SOCIOLOGY AND ITS CONTRIBUTION TO THE RISE OF THE NOVEL - Dahlan Dahlan (Elite : English and Literature Journal, 2014)
AbstractThis paper elaborates  people and and their school who greatly contribute to the development  of literary works, particularly novel. Their contributions inspire authors, critics at the development of ideas of literature, some of them such as: Framkfurt school, Avant Garde, and Genetic structuralism and some schools of critique like Neo Marxian ideology Critique and  Bordieu. This paper also shows how sociology ideas are successfully applied to the literary works.